Analisis Postur Kerja Dokter Gigi pada Klinik Ortodonti Kartini Menggunakan Metode Rosa (Rapid Office Strain Assessment) - Yul, Faradila Ananda; Dana Syafly, Suci (SURYA TEKNIKA, 2023)
Kartini's Orthodontic Practice is a company engaged in the specialized services in the field of dental health. Service that offered by the Kartini Orthodontic Practice is to correct the position of the teeth irregular, monitor the development and growth of teeth and gums, as well as interpreting the results of examinations and existing diagnoses,dental care, such as scaling, overcoming cavities,tooth extraction, and others. The problem that occurs in this clinic is that doctors often experience complaints of pain in the neck, wrists, waist and legs. work posture analysis was carried out using the ROSA (Rapid Office Strain Assessment) method. Based on the results of the work posture assessment using the ROSA method, it shows that 3 of the workers, there is one worker who is found to be at high risk and must be studied further.